Regional Differentiation of The Demographic Potential in Italy and Poland - Pastuszka, Sławomir (Comparative Economic Research. Central and Eastern Europe, 2017)
The aim of this paper is to compare the demographic potential of given Italian and Polish regions. The analysis shows that the demographic situation in Poland, unlike in Italy, is not directly related to the level of development of some regions and their geographical location. In Italy, the unfavorable demographic situation is typical of most of the less-developed southern regions, whereas in Poland it occurs in voivodships with different economic potential, situated in different parts of the country. This is probably the result of the current polycentric development of Poland, characteristic of a centralized economy, and the polar development in Italy. Certain demographic similarities, but of different levels, related to the dynamics of the population, the level of fertility, and net migration are observable in the macro-regions of Mezzogiorno and Eastern Poland.